Effect of Screen Size on Seed Quality in Sunflower - A.V. MUNDE; R.V. MANE; A.P. PATIL; A.B. DESHPANDE (Seed Research, 2026)
Three sunflower varieties viz. SS-56, Morden and EC 68414 were graded with screen size 1.85, 2.50, 2.80 and 4.00 mm (oblong) for different quality parameters. It was observed that screen size 2.50 mm (oblong) gave maximum recovery 90.00, 83.00 and 78.00 per cent, thousand seed weight 44.18, 45.32 and 47.50 g, bulk density 413.7, 414.7 and 405.0 kg/m², physical purity 99.60, 99.48, 98.97 per cent, germination 87.50, 94.50 and 80.40 per cent (well above seed certification standard) and vigour index 1920, 1875, 1870 for SS-56, Morden and EC 68414 varieties, respectively. Hence, it is recommended that screen size 2.50 (oblong) is best for processing of sunflower seed.